360-Degree Feedback: An Innovative Strategy to Measure Students' Soft Skills in the “Asistensi Mengajar” Program - Mentari, Sriyani; Nuraini, Umi; Fauzan, Slamet (International Journal of Essential Competencies in Education, 2025)
Assessing soft skills in Indonesia’s “Teaching Assistance/Asistensi Mengajar” (AM) program remains a challenge, as evaluations have typically focused on teaching performance and relied on self or supervising teacher assessments, overlooking the multidimensional and context-dependent nature of soft skills. This study addresses this gap by implementing a 360-degree feedback model to provide a more comprehensive evaluation of AM participants’ soft skills. Four assessor groups were involved: college students (self-assessment), peers, supervising teachers, and vocational students. Using a descriptive-analytical quantitative design, data were collected from 330 respondents and analyzed with descriptive statistics, the Kruskal–Wallis test, and Dunn’s post hoc test. The results showed that communication received the highest mean self-rating (M = 4.28, SD = 0.60), while adaptation received the lowest (M = 3.85, SD = 0.58). Significant perceptual gaps were found across assessor groups, particularly in adaptation, where students rated themselves lower than peers (Z = 5.00, p < .001, r = .43) and supervising teachers (Z = 2.83, p = .019, r = .24). Conversely, in communication, self-assessments were higher than those of vocational students (Z = 5.12, p < .001, r = .45). These findings demonstrate that assessor perspectives differ systematically, reflecting self-efficacy biases and relational expectations. Practically, the study provides empirical evidence that integrating 360-degree assessments into AM can identify hidden competency gaps and guide targeted training interventions, particularly in adaptation skills, while ensuring that student voices are formally included in program evaluation.